MENANGANI AJARAN SESAT DI KALANGAN UMAT ISLAM: PERSPEKTIF UNDANG-UNDANG DAN PENTADBIRAN - Ismail, Siti Zubaidah (Jurnal Syariah, 2010)
Activities related to deviation from the Islamic teaching is something that is not unheard of in our country. Ever since before Independence, certain groups spread its influence in the society, and many efforts have been done to curb this menace. This article discusses the reality pertaining to solving the problem, by discussing some issues arising out of legal mechanism such as the effect of fatwa, the enforcement and the challenges of meeting with legal requirements of shariah criminal offences enactment. It also shows that such activity can only be curbed through a standardized effort and holistic approach.